2013
DOI: 10.3109/10826084.2013.800116
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Treatment Needs Among Pregnant and Postpartum Women with Substance Use and Depression

Abstract: Little is known about treatment for pregnant and postpartum women with co-occurring substance use and depression. Funded by the National Institute of Drug Abuse, we conducted three focus groups with 18 pregnant and postpartum women in 2011 at an urban substance use treatment clinic. A semi-structured discussion guide probed for factors impacting treatment outcomes and needs. Data were analyzed using grounded theory. Women identified motivational, family, friend, romantic, and agency characteristics as facilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
72
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 31 publications
5
72
0
2
Order By: Relevance
“…For example, results of a randomized clinical trial reported almost 75% of the participants convinced a family member to enter substance use treatment after intervention training (Miller, Myers, & Tonigan, 1999). However, studies examining the role of familial support in substance abuse treatment are mixed (Kuo et al, 2013; Liepman, Nirenberg, & Begin, 1989; Miller, Myers, & Tonigan, 1999). …”
Section: 0 Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, results of a randomized clinical trial reported almost 75% of the participants convinced a family member to enter substance use treatment after intervention training (Miller, Myers, & Tonigan, 1999). However, studies examining the role of familial support in substance abuse treatment are mixed (Kuo et al, 2013; Liepman, Nirenberg, & Begin, 1989; Miller, Myers, & Tonigan, 1999). …”
Section: 0 Introductionmentioning
confidence: 99%
“…However, substance users are more likely to be alienated from their non-using social networks and report significant relational problems (Lemieux, 2002). Kuo and colleagues (2013) found family members to be both supportive and unsupportive. Family members were a source of encouragement and help for remaining abstinent, but were often a source of condescension, judgment, and reinforcement of low self-esteem.…”
Section: 0 Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a qualitative analysis of shared clinical appointments for nonpregnant persons with opioid use disorder found that group care promoted direct emotional support between participants, cultivated a sense of accountability for group members, and a created a supportive community for patients in recovery . The group check‐ins and games in our curriculum foster relationship building between women, which has been shown in previous qualitative analyses to be an important source of support in recovery for pregnant and postpartum women with substance abuse and depression . Sessions on trauma and intimate partner violence were chosen given the high documented rate of prior sexual and physical abuse for pregnant women with opioid use disorder .…”
Section: Group Care Modelmentioning
confidence: 99%
“…Relatedly, HV programs are long-term, often providing services into a child's second or third year of life, allowing for greater continuity of care. Second, pregnancy and the postpartum period are times when many women are especially motivated to change behaviors and life circumstances that may negatively impact their baby (Kuo et al, 2013; Lee King, Duan, & Amaro, 2015). HV programs are inherently voluntary and strength-based, and thus provide a natural framework for capitalizing on this motivation to change.…”
Section: Introductionmentioning
confidence: 99%